Pengaruh Disiplin Belajar dan Kecerdasan Spiritual terhadap Hasil Belajar Agama Buddha Mahasiswa KMB Universitas Swasta Se-DKI Jakarta - Nia Hanliadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
The study adopts a quantitative method approach that aims to find the influence of learning discipline and spiritual intellegence on learning outcome buddhist of KMB’s student from Private University in DKI Jakarta. The population of the study was taken from a population of 274 KMB’s students from Private University in DKI Jakarta, and using random sampling of a sample of 163 students. The findings are; there is a positive and high significant influence of of learning discipline on learning outcome buddhist of KMB’s student from Private University in DKI Jakarta with the result of correlation coefficient is 0,816 ; there is a positive and high significant influence of spiritual intellegence on learning outcome buddhist of KMB’s student from Private University in DKI Jakarta with the result of correlation coefficient 0,255 and there is a positive and high significant effect between learning discipline and spiritual intellegence on learning outcome buddhist of KMB’s student from Private University in DKI Jakarta with the result of correlation coefficient 0,824. The analysis of this testing hypothesis, that the learning discipline and spiritual intellegence carried out by students will have impact on improving tknowledge, application, analysis, value and skill of students so learning outcome buddhist of KMB’s student from Private University in DKI Jakarta become optimal.